Life Cycle Cost and Sensitivity Analysis of Reutealis trisperma as Non-Edible Feedstock for Future Biodiesel Production - Riayatsyah, T.M.I.; Ong, H.C.; Chong, W.T.; Aditya, L.; Hermansyah, H.; Mahlia, T.M.I. (MDPI, 2017)
The use of non-edible, second-generation feedstocks for the production of biodiesel has been an active area of research, due to its potential in replacing fossil diesel as well as its environmentally friendly qualities. Despite this, more needs to be done to remove the technical barriers associated with biodiesel production and usage, to increase its quality as well as to widen the choice of available feedstocks; so as to avoid over-dependence on limited sources. This paper assesses the feasibility of using a local plant, Reutealis trisperma, whose seeds contain a high percentage of oil of up to 51%, as one of the possible feedstocks. The techno-economic and sensitivity analysis of biodiesel production from Reutealis trisperma oil as well as implementation aspects and environmental effects of the biodiesel plant are discussed. Analysis indicates that the 50 kt Reutealis trisperma biodiesel production plant has a life cycle cost of approximately 710 million, yielding a payback period of 4.34 years. The unit cost of the biodiesel is calculated to be 0.69/L with the feedstock cost accounting for the bulk of the cost. The most important finding from this study is that the biodiesel from Reutealis trisperma oil can compete with fossil diesel, provided that appropriate policies of tax exemptions and subsidies can be put in place. To conclude, further studies on biodiesel production and its limitations are necessary before the use of biodiesel from Reutealis trisperma oil may be used as a fuel source to replace fossil diesel.